Forensic Analysis and Security Assessment in Android m-Banking Applications: A Survey - Khavya, K.; Hema Priya, N. (Indian Journal of Computer Science, 2019)
Data is today's gold. Preserving data is important and it is vital to secure one's private information but nowadays, attackers are stealing users' information and selling it to others for various purposes. In today's world, 57% of digital population is using its smart phones and tablets for all bank related transactions and storing its important credentials. However, majority of people prefer android mobile phones due to its low cost. However, as per recent studies, the Android mobiles are 47% prone to high risk vulnerabilities and 76% of the password credentials can be easily traced. Almost 89% of the vulnerabilities can be exploited through malwares. This survey paper investigates forensic analysis and security assessment in Android mobile banking applications and lists a few measures to safeguard the devices from malicious attacks.